Bilin-Dependent Photoacclimation in Chlamydomonas reinhardtii . Issue 11 (30th October 2017) - Wittkopp, Tyler M.; Schmollinger, Stefan; Saroussi, Shai; Hu, Wei; Zhang, Weiqing; Fan, Qiuling; Gallaher, Sean D.; Leonard, Michael T.; Soubeyrand, Eric; Basset, Gilles J.; Merchant, Sabeeha S.; Grossman, Arthur R.; et al.
Abstract : Linear tetrapyrroles (bilins) are needed for light-dependent greening and for assembly and maintenance of a functional photosynthetic apparatus in the green alga Chlamydomonas. Abstract: In land plants, linear tetrapyrrole (bilin)-based phytochrome photosensors optimize photosynthetic light capture by mediating massive reprogramming of gene expression. But, surprisingly, many green algal genomes lack phytochrome genes. Studies of the heme oxygenase mutant ( hmox1 ) of the green alga Chlamydomonas reinhardtii suggest that bilin biosynthesis in plastids is essential for proper regulation of a nuclear gene network implicated in oxygen detoxification during dark-to-light transitions. hmox1 cannot grow photoautotrophically and photoacclimates poorly to increased illumination. We show that these phenotypes are due to reduced accumulation of photosystem I (PSI) reaction centers, the PSI electron acceptors 5′-monohydroxyphylloquinone and phylloquinone, and the loss of PSI and photosystem II antennae complexes during photoacclimation. The hmox1 mutant resembles chlorophyll biosynthesis mutants phenotypically, but can be rescued by exogenous biliverdin IXα, the bilin produced by HMOX1. This rescue is independent of photosynthesis and is strongly dependent on blue light. RNA-seq comparisons of hmox1, genetically complemented hmox1, and chemically rescued hmox1 reveal that tetrapyrrole biosynthesis and known photoreceptor and photosynthesis-related genes are not impacted in the hmox1 mutant at the transcript level. We propose that a bilin-based, blue-light-sensing system within plastids evolved together with a bilin-based retrograde signaling pathway to ensure that a robust photosynthetic apparatus is sustained in light-grown Chlamydomonas.